A pilot randomized controlled trial of neuromodulation-augmented balance training in people with multiple sclerosis: STIM-Balance Protocol - Shirin Tajali; Jillian Scandiffio; Yasma Ali-Hassan; Derrick Lim; Rayna Ghosh; Sharmini Atputharaj; Kristin Musselman; Robert Simpson; Kei Masani (PLoS ONE, 2026)
Background Impairments in balance control and falls are common problems for people with multiple sclerosis (PwMS), resulting in mobility limitations and reduced participation. Non-invasive neuromodulation techniques such as functional electrical stimulation (FES) and transcutaneous spinal stimulation (TSS) have revealed promising results in improving motor functions in other neurological populations; however, their effects during task-specific balance training have not been investigated in PwMS. Objective To evaluate the feasibility, acceptability, safety, and preliminary clinical efficacy of neuromodulation-augmented balance training programs on balance, mobility, and neuroplasticity in PwMS (ClinicalTrials.gov Identifier: NCT07174973). Methods Twenty-four ambulatory PwMS will be randomly assigned into three groups: (1) visual feedback balance training (VFBT) with sham stimulation, (2) VFBT with active (closed-loop) FES for the ankle muscles and sham TSS, and (3) VFBT with active FES and active (open-loop sub-motor-threshold) TSS at the lumbosacral enlargement. Participants in each group will complete 12 training sessions over six weeks. Feasibility, safety, and acceptability will be assessed through recruitment and adherence metrics, adverse-event monitoring, and semi-structured interviews guided by the Technology Acceptance Model questionnaire-2. Performance-based measures of balance, mobility, and walking speed, as well as patient-reported outcomes of balance confidence, walking ability, and fear of falling will be recorded to assess the preliminary efficacy. Modulation in neural pathways excitability will be quantified by recording motor evoked potentials and spinal motor evoked potentials. Conclusion Findings will help to determine whether neuromodulation-augmented balance training is feasible, safe, and acceptable for PwMS and will guide the design of a future fully powered RCT.